A case of Adie’s tonic pupil - Ocak, Özgül; Zan, Burak; Ocak, Barış (Journal of Surgery and Medicine, 2021)
Adie’s tonic pupil, the round unilateral tonic pupil, is a neuro-ophthalmologic disorder with dilation and no light response. Although usually idiopathic, it may be associated with infection, inflammation, and postganglionic paraneoplastic nerve damage. It is called Holmes-Adie syndrome when deep tendon reflex loss accompanies Adie’s tonic pupil. The diagnosis is made by observing a miotic response after dilated pilocarpine instillation. Spontaneous recovery depends on etiological factors.